PENGARUH VOLUME PERDAGANGAN SAHAM, DEPOSITO DAN KURS TERHADAP IHSG BESERTA PREDIKSI IHSG (MODEL GARCH DAN ARIMA) - Etty Murwaningsari (Journal of Indonesian Economy and Business (JIEB), 2008)
The objective of this research is to identify the influences of stock trading volume, deposits and exchange rate to the stock price index (IHSG). This research examines secondary data from Indonesia Stock Exchange Reference Center for monthly IHSG from 1992-2006 as well as deposit interest rate and exchange rate from Bank of Indonesia at the same period. The statistical modelings used to test the hypothesis are GARCH and ARIMA Model. Hypothesis test 1 and 3 shows that the stock trading volume has positive influence, while interest rate has negative influence to the stock price index. Test on hypothesis 2 indicates that exchange rate has no significant influence to stock trading volume. Based on the prediction obtained by ARIMA and GARCH method, it is shown that ARIMA provides the least differences between actual value and predicted value. It is concluded that for our data, ARIMA method is better than GARCH method.